The Effect of Ownership Structure on The Stability of Sharia Commercial Banks in Indonesia - Mochamad Rizki Ramdani; Marwansyah Marwansyah; Muhamad Umar Mai (Publikasi Indonesia, 2026)
The stability of Islamic banking is a strategic issue considering its role in supporting the national financial system while maintaining compliance with Sharia principles. This article analyzed the effect of ownership structure on the stability of Sharia Commercial Banks (Bank Umum Syariah / BUS) in Indonesia based on the perspectives of agency theory and stakeholder theory. The ownership structures examined included ownership concentration, government ownership, foreign institutional ownership, and domestic institutional ownership, with the capital structure proxied by the Debt-to-Equity Ratio (DER) as a control variable. Bank stability was measured using the Z-score indicator. This study employed a descriptive quantitative approach with panel data regression analysis using annual data from Sharia Commercial Banks registered with the Financial Services Authority (Otoritas Jasa Keuangan / OJK) during the 2015–2024 period. The census sampling technique resulted in 92 observations from 12 banks. The random-effects model regression results showed that government ownership and domestic institutional ownership had positive and significant effects on BUS stability, while ownership concentration, foreign institutional ownership, and DER had no significant effects. Domestic institutional ownership was identified as the most dominant variable influencing bank stability. These findings indicated that the stability of Islamic banking in Indonesia was more strongly determined by the effectiveness of internal oversight, corporate governance practices, and the long-term orientation of domestic investors rather than by foreign ownership or the degree of ownership concentration.